2016
DOI: 10.1007/978-981-10-1498-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in Cancer Immunology

Abstract: Cancer immunology is the study of interaction between cancer cells and immune system by the application of immunology principle and theory. With the recent approval of several new drugs targeting immune checkpoints in cancer, cancer immunology has become a very attractive field of research and is thought to be the new hope to conquer cancer. This chapter introduces the aberrant expression and function of noncoding RNAs, mainly microRNAs and long noncoding RNAs, in tumor-infiltrating immune cells, and their sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Their unique features include regulation of multiple targets, ability to be secreted into the extracellular space, and the communication linking capacity between tumor cells and the TME. Therefore, studying miRNAs concerning the complex interactions between the tumor cells and their microenvironment is necessary for understanding the tumor progression and, thus, the development of new therapeutic strategies ( Kros et al, 2014 ; Kohlhapp et al, 2015 ; Li and Liu, 2016 ).…”
Section: Microglia and Astrocytes’ Role In Glioblastoma Malignancymentioning
confidence: 99%
“…Their unique features include regulation of multiple targets, ability to be secreted into the extracellular space, and the communication linking capacity between tumor cells and the TME. Therefore, studying miRNAs concerning the complex interactions between the tumor cells and their microenvironment is necessary for understanding the tumor progression and, thus, the development of new therapeutic strategies ( Kros et al, 2014 ; Kohlhapp et al, 2015 ; Li and Liu, 2016 ).…”
Section: Microglia and Astrocytes’ Role In Glioblastoma Malignancymentioning
confidence: 99%
“…WFDC21P, namely lnc-dendritic cell (lnc-DC) has been observed to be exclusively expressed in human DCs and mediates the differentiation of monocytes to DCs via the activation of signal transducer and activator of transcription 3, which is a transcription factor that regulates numerous immune-associated genes ( 25 , 26 ). Wu et al ( 27 ) suggested that lnc-DC in plasma may be a possible biomarker for systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…(5) other unconventional miRNA functions (44). Despite the continued emergence of new species, nowadays, most reports are focused on miRNA and lncRNA and great progress has been made (45).…”
Section: The Achievement In This Fieldmentioning
confidence: 99%